PELATIHAN SELF-COMPASSION UNTUK MENGURANGI SELF-CRITICISM PADA MAHASISWA - Amita, Nindy; Siregar, Juliarni; Listyani, Nilla (JIP (Jurnal Intervensi Psikologi), 2024)
High self-criticism among students occurs due to increasing responsibilities, competitive demands in various aspects of life, and academic pressure. This study aims to determine the effect of self-compassion training on reducing self-criticism in students. The research used a group pre-test and post-test design. The subjects were ten students from the Islamic University of Riau. We used a self-criticism scale, The Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS) developed by Gilbert (2004). To evaluate changes in self-criticism among students, we applied the Wilcoxon test. Statistical results were obtained using the Wilcoxon Normality Test, which yielded a value of 0.005<0.05. It can be concluded that there are significant differences between the pre-test and post-test results. Self-compassion training has an impact on reducing self-criticism in students. The influence of the training provided can be understood and implemented by participants, allowing them to gain better self-understanding.